Injury Risk in International Rugby Union: Three-Year Injury Surveillance of the Welsh National Team. Issue 7 (27th July 2015) - Moore, Isabel S.; Ranson, Craig; Mathema, Prabhat
Background: Within international Rugby Union, only injury rates during the Rugby World Cup have been reported. Therefore, injury rates and types during other international tournaments are unknown. Purpose: To assess the 3-year incidence, severity, nature, and causes of match and training injuries sustained during different international tournaments played by the Welsh national Rugby Union team. Study Design: Descriptive epidemiology study. Methods: Injury data for all players (n = 78) selected for 1 national Rugby Union team over a 3-year period were analyzed using the international consensus statement methods. Player height (cm) and mass (kg) were recorded. Tournaments were grouped for comparisons as: autumn tournaments (2012 and 2013), Rugby World Cup (RWC; 2011), Six Nations (2012, 2013, and 2014), and summer tournaments (2012, 2013, and 2014). Injury incidence (injuries/1000 hours), prevalence (% of players unavailable), and severity (days lost) were calculated for each tournament. Injury location, type, and cause of match and training injuries were analyzed. Results: Match injury incidence was highest during autumn tournaments (262.5/1000 match-hours) and lowest during the RWC (178.6/1000 match-hours). Summer tournaments had the highest training incidence (5.5 injuries/1000 training-hours). Mild injuries were most likely during the RWC (risk ratio [RR], 2.02; 95% CI, 1.26-3.24), while severe injuries were most likely during autumn tournaments (RR, 3.27; 95% CI, 1.70-6.29). Quadriceps hematomas (18.8/1000 match-hours; 95% CI, 11.3-31.1) and concussions (13.8/1000 match-hours; 95% CI, 7.6-24.8) were the most common match injuries, with shoulder dislocations being the most severe (111 mean days lost per injury). Conclusion: Injury rates were considerably higher than those previously reported for multiple teams during RWC tournaments. Further investigation of injury rates and risk factors is recommended to accurately gauge their impact within international Rugby Union, particularly with regard to lower limb hematoma, concussion, and shoulder injuries.